Role of dipA and pilD in Francisella tularensis Susceptibility to Resazurin - Kendall Souder; Emma J. Beatty; Siena C. McGovern; Michael Whaby; Emily Young; Jacob Pancake; Daron Weekley; Justin Rice; Donald A. Primerano; James Denvir; Joseph Horzempa; Deanna M. Schmitt (MDPI AG, 2021)
The phenoxazine dye resazurin exhibits bactericidal activity against the Gram-negative pathogens Francisella tularensis and Neisseria gonorrhoeae. One resazurin derivative, resorufin pentyl ether, significantly reduces vaginal colonization by Neisseria gonorrhoeae in a mouse model of infection. The narrow spectrum of bacteria susceptible to resazurin and its derivatives suggests these compounds have a novel mode of action. To identify potential targets of resazurin and mechanisms of resistance, we isolated mutants of F. tularensis subsp. holarctica live vaccine strain (LVS) exhibiting reduced susceptibility to resazurin and performed whole genome sequencing. The genes pilD (FTL_0959) and dipA (FTL_1306) were mutated in half of the 46 resazurin-resistant (RZR) strains sequenced. Complementation of select RZR LVS isolates with wild-type dipA or pilD partially restored sensitivity to resazurin. To further characterize the role of dipA and pilD in resazurin susceptibility, a dipA deletion mutant, ΔdipA, and pilD disruption mutant, FTL_0959d, were generated. Both mutants were less sensitive to killing by resazurin compared to wild-type LVS with phenotypes similar to the spontaneous resazurin-resistant mutants. This study identified a novel role for two genes dipA and pilD in F. tularensis susceptibility to resazurin.